(untitled) (Research, Society and Development, 2020)
This article aims to present the traditional knowledge from an amazon community about the use of Mexican mint plant as a health alternative complement and insert this knowledge in a curricular proposal for basic education. In order that, it was necessary to do a qualitative descriptive research for knowledge survey about the use of the plant, 25 key informants in Caeté Basin participated in interviews, observations and a standardized form, besides vegetal sampling was collected for botanic identification. Plectranthus amboinicus Lour widely known as “Hortelã Grande” in Camutá is used to treat respiratory complications through its leaves. The species has chemical compounds as carvacrol and thymol that has mycrobial, fungitoxic and antitumor activities. This traditional and scientific knowledge enabled the construction of a curricular proposal that involves the subjects Portuguese Language, Geography and History, Religious Education, Sciences and Mathematics through the web of knowledge in Paulo Freire.